The Revolutionary Spirit - Jennings, Willie James 1961- (2025)
This response to the reviews of the author’s Acts commentary focuses on the divine flow of the Spirit, which transforms human relationships and movements, guiding believers into new realities of belonging, intimacy, and shared care that transcend traditional boundaries of identity, race, and social constructs and idolatrous conceptions of coupling and family structure. Acts reveals a God who creates movement, connection, and life, challenging human resistance to divine newness.
Keywords: Embodiment; Political Theology; Intimacy; Belonging; Pneumatology; divine flow; Holy Spirit